Structural Design and Simulation Analysis of Eight-wheeled Robot with Passive Swing Arm - Yang Wulin; Zhang Jing; Zhang Junjun (Jixie chuandong)
In order to improve the terrain adaptability， obstacle-climbing capability and operability of wheeled mobile robots， an eight-wheeled robot with passive swing arms is designed. The articulated rocker arm can passively adapt to the change of the terrain and rotate relatively， and a flexible joint at the hinge point is introduced to generate a resistive torque， to improve the stability of the robot. The obstacle-climbing mechanism of this robot on vertical step is analyzed. The obstacle-climbing simulation is carried out by using the RecurDyn， the simulation results show that the robot can climb the vertical step beyond the diameter of the wheel. The feasibility of flexible joints is verified by simulation comparison experiments with and without flexible joints， and the optimal design parameters are obtained， a theoretical basis for the development of physical prototype is provided.